2012
DOI: 10.1155/2012/749540
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for the End-Bearing Capacity of Tapered Piles Using Cavity Expansion Theory

Abstract: On the basis of evidence from model tests on increasing the end-bearing behavior of tapered piles at the load-settlement curve, this paper proposes an analytical spherical cavity expansion theory to evaluate the end-bearing capacity. The angle of tapering is inserted in the proposed model to evaluate the end-bearing capacity. The test results of the proposed model in different types of sands and different relative densities show good effects compared to conventional straight piles. The end-bearing capacity inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Despite these relatively small loads in non-uniform piles, Table 4 indicates that the unit toe resistance of non-uniform piles is at least 100% larger than that of uniform piles at the same level of pile head displacement. Thus, it is revealed that tapering the pile affects both side and tip behavior of piles, as also found by Manandhar and Yasufuku (2012).…”
Section: Taper Effect On Pile Tip Loadssupporting
confidence: 67%
“…Despite these relatively small loads in non-uniform piles, Table 4 indicates that the unit toe resistance of non-uniform piles is at least 100% larger than that of uniform piles at the same level of pile head displacement. Thus, it is revealed that tapering the pile affects both side and tip behavior of piles, as also found by Manandhar and Yasufuku (2012).…”
Section: Taper Effect On Pile Tip Loadssupporting
confidence: 67%
“…Multiple authors have approached the behavior of variable cross-section elements with analytical solutions [5,14,26,[30][31][32][33][34]. For instance, Eisenbergb [14] presented a formulation to analyze beams with variable cross-section.…”
Section: Analytical Solutionsmentioning
confidence: 99%
“… Geometric alternatives to support structures—Foundation geometry is a defining factor for total loading capacity and pile displacement ( Frost et al, 2017 ). Conical piles provide an increased bearing capacity compared to straight-sided cylindrical piles ( Manandhar and Yasufuku, 2012 ). The lateral surface texture of foundation piles is another parameter to increase loading capacity by increasing shear strength of its interface with soil ( Martinez and Frost, 2017 ).…”
Section: Application Of Root Biology To Technical Designsmentioning
confidence: 99%